Aesthetic and Functional Mandibular Reconstruction With Immediate Dental Implants in a Free Fibular Flap and a Low-Profile Reconstruction Plate: Five-Year Follow-up. Issue 4 (April 2015) - Shen, Yu-Fu; Rodriguez, Eduardo D.; Wei, Fu-Chan; Tsai, Chi-Ying; Chang, Yang-Ming
Abstract : Background: Aesthetic and functional mandibular reconstruction can be achieved in 1-stage. It involves simultaneous dental implant placement in a free vascularized fibula transfer with a low-profile reconstruction plate. The aim of this study was to assess the postoperative aesthetic profile and oral functional result. Material and Methods: Ten patients with a mean age of 31.6 years and an average follow-up time of 83.7 months underwent 1-staged mandibular reconstructions after segmental mandibulectomies. Simultaneous dental implantation was placed at the fibular segment according to the maxillary dentition. The fibula-implant construct was stabilized superiorly with miniplates and an additional low-profile reconstruction plate recreated the inferior mandibular contour. Any remaining vascularized soft tissue was used for augmentation. Palatal mucosa grafts were placed around the dental implant healing abutment at the uncovering stage surface. Aesthetic profile and oral function were evaluated postoperatively for 5 years. Results: All microsurgical transplantations were successful. None of the patients required subsequent revisions. All patients completed prosthodontic rehabilitation. All patients had palatal mucosal grafts placed around the dental implants. The mean probing pocket depths were shallower around the implants, 3.09 ± 0.82 mm at mesial, 3.33 ± 1.05 mm at distal, 3.02 ± 1.13 mm at buccal, and 3.23 ± 1.17 mm at lingual surfaces. Radiographs revealed no statistical differences in mean of the mesial [0.27 ± 0.26 mm] and distal [0.33 ± 0.25 mm] of peri-implant bone loss. The prosthetic load mean follow-up time was 71.7 months with a satisfactory implant-supported prosthesis. Two slender female patients palpated the reconstruction plate beneath the soft tissue envelope. Conclusions: This approach is selectively fashioned for patients with benign disease when the overlying soft tissue drape is adequate. The technique described results in improved appearance and function through definition of the lower third of the face and simultaneous dental implant replacement.